Regenerative Endodontic Treatment in Teeth with Internal Root Resorption: An Insight Over the Available Literature - Aamil Ashraf; Ruth Pérez Alfayate (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
Internal root resorption (IRR) is a resorptive defect of the root's internal aspect, and its pathogenesis occurs because of the activity of odontoclasts. If left untreated, IRR will eventually cause necrosis of the pulp tissue apical to the resorptive lesion, leading to periapical pathologies and resistance failure of the tooth. Treatment of this kind of pathology encompasses many options ranging from conventional root canal treatment to endodontic surgery. The most recent innovation for the treatment of IRR is revascularization. The present review aims to discuss revascularization as a treatment option for IRR. An extensive search for recent available data regarding this kind of treatment and potential suggestions for the future have been made. Revascularization of teeth with IRR has promising results and should be considered a choice for treating IIR cases as an alternative to conventional root canal treatment.